Academic and research writing: essential skills and styles - Dutta, Sanjay Kumar (New Century Publications, 2018)
Whether you are writing a business e-mail or a research paper, the present work will assist you in becoming a better writer in English. In short, this book is a rich resource for anyone who needs to communicate in English effectively.